Patient With Advanced Aggressive B2 Thymoma Achieved Positive Outcomes Post CAP‐Endostar Combination Therapy - Min Zhang; Jingjing Zhang; Kelei Zhao; Xiaohan Yuan; Jinghang Zhang; Yanting Liu; Ping Lu (The Clinical Respiratory Journal, 2025)
ABSTRACT This case report features a patient with an invasive thymoma. The patient presented with an anterior mediastinal mass that invaded the left brachiocephalic trunk vein, resulting in the formation of a carcinoma thrombus in the right atrium, superior vena cava, left brachiocephalic trunk vein, and left internal jugular vein (Masaoka stage IV). No indication for surgery was assessed by surgical consultation. After six cycles of chemotherapy and chest radiotherapy, the tumor size decreased from 72.43 to 24 mm, showing a significant improvement in patient efficacy. After a follow‐up of 50 months, the patient remained well, without local recurrence or distal metastasis, and maintained a partial response (PR).